Avaliação da incorporação de agregado reciclado na composição de concretos autoadensáveis - Kuster Junior, Jocimar Souza (Universidade Federal de São Carlos, 2018)
Self-compacting concrete has specific characteristics that differ from conventional concrete. Its self- compacting capability, ease of pumping, excellent homogeneity and resistance to segregation are highlighted, being these characteristics obtained by its composition. On the other hand, the recycling of waste from civil construction has aroused great interest and consolidated as an important practice for the sustainability of the construction sector, by reducing the environmental impact generated. Among the purposes that have generated great interest is the use of construction waste as a recycled aggregate. In this way, the present study tried to evaluate the influence of the substitution of the natural aggregates for recycled (big and small). The dosage of self-compacting concrete was performed according to the method proposed by Alencar and Helene. From the reference trace (AN REF), three traces were produced with 30%, 50% and 100% recycled aggregate replacement (AGR 30, AGR 50 and AGR 100) and 2 traces with substitution contents of the recycled kid's aggregate of 30% and 50% (AMR 30 and AMR 50). Tests were carried out in the fresh state of the mixture for determination of scattering and run-time, visual stability index, passing ability by ring method J, passing through L method, viscosity by funnel V method and resistance to segregation by the segregation column method, to verify the self-density of the concretes. In the hardened state, tests were performed to determine the resistance to simple compression, tensile strength by diametrical compression, modulus of elasticity, absorption of water by immersion, voids index and specific mass. The concretes produced presented satisfactory performance in the fresh state, being considered self - supporting. As for the mechanical behavior, the concretes presented resistance to compression similar or even superior to the reference concrete. The modulus of elasticity decreased as the substitution content of the recycled aggregates increased. The results of water absorption by immersion and voids index increased as the substitution content of the recycled aggregates increased. Through the present study, it can be seen that the incorporation of recycled aggregates (large and small) from construction waste is an alternative for the production of self-supporting concrete.
Evaluation of the incorporation of recycled aggregate in the composition of self-supporting concretes
Keywords: Concreto autoadensável; Agregado reciclado; Dosagem; Propriedades mecânicas; Self-compacting concrete; Recycled aggregate; Dosage; Mechanical properties; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS